ANALYTICAL STUDY OF GANDHAKAAJEERNA BADDHO RASA THROUGH XRD, SEM, EDS, ZP AND PA - Kumar Saikrishna; Ch. Sridurga. (International Journal of Applied Ayurved Research, 2016)
Rasa Shastra deals with medicinal aspects of metals, minerals, precious stones and poisonous plant drugs. It has been serving humanity from centuries with its unique metallic and herbo-mineral formulations. The Rasaushadhies have wide range of therapeutic efficacy and innate qualities like quick action, less dose, palatability, and prolonged shelf life. “Gandhakaajeernabaddho Rasa” (GABR) is one such herbo-mineral formulation described to have ability to cure almost all types of diseases when given with suitable anupana (vehi-cle). The main ingredients are Parada, Gandhaka, Kakamachi, Tambula, Dathura and Meghanada. In this study the drug GABR was prepared and analysed through X-ray diffraction (XRD), Scanning electron microscope (SEM), Energy dispersive X-ray analysis (EDS/EDX), Zeta potential (ZP) and Particle size analysis (PA). XRD revealed that the GABR consists of Hgs (Meta Cinnabar) majorly and Sulphur in minor without any free mercury traces. SEM revealed that the GABR contains Mer-cury 6.25%, Sulphur 44.95%, Carbon 41.75%, Oxygen 6.64% and Potassium 0.44% by weight. ZP mean was -86.3mV which indicates the high colloidal stability. The mean particle size of the particles is 7nm with standard deviation of 0.47 nm. The details analytical study (i.e, XRD, SEM, EDS, ZP and PA) of Gandhakaajeernabaddho Rasa will be discussed in the full paper.